Analisa dan Implementasi Metode Zhang-Suen Dalam Pengerangkaan (Skeleton) Pada Citra Untuk Mengurangi Redundant - Rahayu, Annisa (STMIK Budi Darma, 2020)
Zhang-Suen is an algorithm for the process of framing an image. This process is often applied to pre-thinning, for example, the initial stages in the pattern recognition process. This is implemented by changing the initial image with binary patterns to represent the framework. In a line-shaped image, the skeleton shows all the information from the original object. The components of the skeleton, namely the position, orientation, and length of the skeleton line segments represent the lines that form the image. These components make it easy to characterize the components of the image. In a line-shaped image, the skeleton shows all the information from the original object. The components of the skeleton, namely the position, orientation, and length of the skeleton line segments represent the lines that form the image. In the process of working on this thesis the software used is MATLAB. MATLAB is a software with a high programming language. The final results of this thesis are sharpened edges. In doing the thesis using the Zhang-Suen method.